Understanding the mechanisms of microstructure refinement and plasticity enhancement of M50 bearing steel fabricated by the electrical pulse assisted cold ring rolling technology - Fei Yin; Yuxuan Yi; Yu Chen; Gary J. Cheng; Lin Hua (Journal of Materials Research and Technology)
The conventional manufacturing of aeroengine bearing rings, essential components in aircraft engines, is constrained by the poor plastic deformability and pronounced cold work hardening of M50 steel at room temperature. To overcome these limitations, this study proposes an innovative Electrical Pulse-assisted Cold Ring Rolling (EP-CRR) technique that leverages the electroplasticity effect to fabricate high-performance M50 bearing rings with enhanced microstructural and mechanical characteristics. Compared to conventionally cold-rolled (CRRed) counterparts, EP-CRRed M50 rings subjected to pulsed current exhibit significantly refined microstructures, characterized by the formation of numerous subgrains within parent ferrite grains. This microstructural refinement is attributed to the accelerated recrystallization induced by the applied electrical pulses, which promote dislocation mobility and reduce nucleation energy barriers. Furthermore, EP-CRRed rings show a marked reduction in micro- and nanoscale voids, typically arising from the uncoordinated deformation between carbide and ferrite phases. This void mitigation is facilitated by pulse current-induced carbide dissolution, which enhances phase deformation compatibility. Residual stress analysis reveals that EP-CRRed rings exhibit lower overall residual stress and reduced stress heterogeneity compared to CRRed rings. The EP-CRR process effectively alleviates cold work hardening by promoting dynamic dislocation processes and stress homogenization, thereby improving plasticity and mechanical stability. These findings demonstrate the potential of EP-CRR technology to advance the forming capability and service performance of aeroengine bearing components, offering a promising pathway for high-strength steel applications in the aerospace sector.